Swimming and swarming motility properties of peanut-nodulating rhizobia - Vicario, Julio César (2015)
Motility allows populations of bacteria to rapidly reach and colonize new microniches or microhabitats. The motility ofrhizobia (symbiotic nitrogen-fixing bacteria that nodulate legume roots) is an important factor determining theircompetitive success. We evaluated the effects of temperature, incubation time, and seed exudates on swimming andswarming motility of five strains of Bradyrhizobium sp. (peanut-nodulating rhizobia). Swimming motility was increased byexudate exposure for all strains except native Pc34. In contrast, swarming motility was increased by exudate exposure fornative 15A but unchanged for the other four strains. All five strains displayed the ability to differentiate into swarm cells. Morphological examination by scanning electron microscopy showed that the length of the swarm cells was variable, butgenerally greater than that of vegetative cells. Our findings suggest the importance of differential motility properties ofpeanut-nodulating rhizobial strains during agricultural inoculation and early steps of symbiotic interaction with the host.